Variasi Waktu Aktivasi terhadap Kualitas Karbon Aktif Tempurung Kelapa - Dame Agunantri Suryani; Faizah Hamzah; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to obtain the right activation time in making coconut shell activated carbon. This research used a Completely Randomized Design with five treatments and four replications which followed by Duncan’s New Multiple Range Test at level 5%. The treatments of this research were KA1 (20 hours activation time), KA2 (22 hours activation time), KA3 (24 hours activation time), KA4 (26 hours activation time) and KA5 (28 hours activation time). Analysis observed were rendement, water content, ash content, pure carbon and iodine adsorption. Analysis result showed that the variety of activation time did not significantly affected on the yield but significantly affected on the water content, ash content, pure carbon and iodine adsorption. The choosen treatment of activated carbon was 28 hours activation with rendement 95.58%, water content 7.02%, ash content 4.49%, pure carbon 80.79% and iodine absorption 782.62 mg/g. Keywords: Activated carbon, coconut shell, activation time.